Pengaruh Penggunaan Media Pembelajaran Doratoon Terhadap Hasil Belajar Siswa Mata Pelajaran Bahasa Indonesia Kelas IV Di SD Negeri 259 Samboang Kabupaten Bulukumba - Hasbia Dg Puji; Aliem Bahri; Irmawati Thahir (Indonesian Journal of Education and Learning, 2026)
The use of Doratoon media in Indonesian language learning can provide an alternative way to motivate students to study more diligently. The research problem in this study is: Does the use of Doratoon learning media affect the learning outcomes of Grade IV students at SD Negeri 259 Samboang, Bulukumba Regency? The purpose of this study is to determine the effect of using Doratoon learning media on the learning outcomes of Grade IV students at SD Negeri 259 Samboang, Bulukumba Regency. This research is an experimental study using a one-group pretest-posttest design. The population in this study consists of Grade IV students, totaling 14 students. The study was conducted from January 2025 to March 2025. Based on the research results and data analysis, it has been proven that there is a positive effect on the learning outcomes of Grade IV students at SD Negeri 259 Samboang. This can be seen from the students' learning outcomes through descriptive statistical analysis: before using Doratoon media, the average student score was still low, whereas after using Doratoon media, the average score was in a higher interval. It was found that the post-test score, which was 77.86, was higher than the pre-test score, which was 45.71. Therefore, it can be concluded that the use of Doratoon learning media has a positive effect on students' learning outcomes in the Indonesian language subject at SD Negeri 259 Samboang, Bulukumba Regency.